DEVELOPMENT OF INTERACTIVE LEARNING MEDIA IN BASIC IPS CONCEPT COURSES IN UNIVERSITIES - Laelia Nurpratiwiningsih; Prasetyo Yuli Kurniawan (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
Research objectives include: (1) analyzing the needs of lecturers and students related to learning media, (2) producing learning media that are worthy of use in learning, and (3) determining the effectiveness of interactive learning media for the basic concepts of IPS in higher education. This research is development research conducted through 7 stages. These stages are the analysis of potential problems, information collection, product design, design validation, design revision, product creation, and limited product trials. Research instruments were given to lecturers and students during the learning of basic concepts of IPS. Data collection techniques included interviews, documentation, observations, questionnaires, and tests. Data analysis techniques consisted of media needs analysis, validation tests, and product effectiveness tests. The results showed that: (1) the analysis of the needs of basic concept learning media of IPS in universities is demonstrated by the results of materials and presentations delivered in full; (2) the development of interactive learning media in the basic concept course of IPS is feasible for students and lecturers in higher education; and (3) the maturity of interactive learning media is effective in IPS learning. This is seen from the results of the study showing that 0.001.